O que se diz na mídia desses leitores improváveis: moradores de rua e sobreviventes da reciclagem de lixo - Santana, Julia dos Santos (Universidade Federal de São Carlos, 2021)
In this work, we present the continuity of analysis and results obtained in our Scientific Initiation research entitled "Infamous Readers: Garbage collectors and homeless people and their representations in the media as a reading community", whose main objective is that of analyzing and demonstrating how certain discursive representations of reading practices attributed to unexpected readers are constructed in the media, to subjects who, living on the margins of society, are not considered as potential readers and who, once identified with books, become they make news, namely, people who make a living from collecting and recycling garbage and homeless people. The set of texts that make up our corpus of analysis is the result of a survey of texts via general internet search engines or from the media institutions themselves, from newspapers and magazines, but also from personal and/or institutional news blogs. We found that these representations of these readers are textualized in different discursive genres, such as news, reports, interviews. We observe the great regularity in the way these representations of reading and readers are presented in these texts. Reading is always presented in its saving, redemptive facet. Readers are presented as individuals who 'decide', who 'choose' to become readers, who read mainly printed books, particularly literature, do so for pleasure and for their education, and find in reading a way to change their lives. Our analyzes of this material are based on the principles of the French Discourse Analysis, the Cultural History of Reading and also on some postulates of the History of Emotions.
What is said in the media of these unlikely readers: homeless people and survivors of garbage recycling
Keywords: Discursos sobre a leitura; Leitores infames; Livro no lixo; Moradores de rua e Catadores de lixo; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA